Electrochemical Deposition of U and RE Elements Using the Stirred Liquid Cadmium Cathode in LiCl-KCl Molten Salts. (28th October 2021) - Kim, Gha-Young; Lee, Chang Hwa; Yoon, Dalsung; Jang, Junhyuk; Lee, Sung-Jai
Abstract : This study was conducted in an attempt to understand the effect of a stirred liquid cadmium cathode (LCC) on the electrodeposition of U and U/RE on Cd. For this purpose, a series of electrowinning tests were performed using an LCC equipped with a Cd stirrer. Initially, three runs of the U electrodeposition tests were conducted using LiCl-KCl-UCl3 at 500°C under a constant current. From the results obtained from the initial three runs, it was found that the maximum deposited amount of U was 7.4 wt% U/Cd. U dendrite formation on the LCC crucible was not observed across each of the three runs. Three additional runs were conducted using LiCl-KCl-UCl3 -RECl3 to determine the extent of U/RE electrodeposition. The maximum number of moles of U + RE metals deposited was 0.07, a value estimated to be 2.14 times higher than the solubility limits exhibited by these metals in Cd. The results of this study show that the use of a Cd stirrer significantly improves the extent of U deposition.